ChemInform Abstract: Unactivated C(sp3)—H Hydroxylation Through Palladium Catalysis with H2O as the Oxygen Source. Issue 6 (21st January 2016) - Hu, Jiantao; Lan, Tianlong; Sun, Yihua; Chen, Hui; Yao, Jiannian; Rao, Yu
Abstract: A new procedure is elaborated for the Pd‐catalyzed hydroxylation of amides such as (I), (III), (VIII), and (X).